Calendar of the fine rolls of the reign of Henry III. Volume II: 1224-1234 - Dryburgh, Paul; Hartland, Beth; Ciula, Arianna ca. 20./21. Jh; Vieira, José Miguel (Boydell Press, 2008)
First ever translation of the Fine Rolls makes documents of crucial importance for study of the period fully available for the first time. The Fine Rolls were the earliest rolls kept by the English royal chancery. Recording offers of money to the king for all manner of concessions and favours, they are central to the study of political, governmental, legal, social and economic history. The reign of Henry III [1216-1272] is a particularly rich period for surviving documents; there are some 56 rolls preserved in the National Archives, one for each regnal year. However, despite the light they shed on politics, government, and society, they have never previously been properly edited or published, and these fully-indexed volumes - covering the period up to 1248 - will therefore be widely welcomed. The Latin rolls are presented in English translation, with all identifiable place-names modernised, although the original forms are preserved; and each volume includes full person, place and subject indexes. This second volume covers as importantand dramatic a period of English history as does the first. The years between 1224 and 1234 witnessed the issue of the final and definitive version of Magna Carta, the ending of the king's minority, his French campaign of 1230,the fall of the justiciar, Hubert de Burgh in 1232, the subsequent regime of Peter des Roches, bishop of Winchester, the civil war which followed Peter's apparent defiance of Magna Carta, and finally in 1234 the restoration of lawful consensual rule
Title from publisher's bibliographic system (viewed on 10 Mar 2023)
v. 1. 1 to 8, Henry III, 1216-1224 -- v. 2. 9 to 18 Henry III, 1224-1234 -- v. 3. 19 to 26, Henry III, 1234-1242
Keywords: Henry / III / King of England / 1207-1272; Fine-rolls; Great Britain / History / 13th century / Sources; England / Genealogy / Sources